Research progress on astrocyte autophagy in ischemic stroke - Su, Pei-Wei; Zhai, Zhe; Wang, Tong; Zhang, Ya-Nan; Wang, Yuan; Ma, Ke; Han, Bing-Bing; Wu, Zhi-Chun; Yu, Hua-Yun; Zhao, Hai-Jun; Wang, Shi-Jun (Frontiers in Neurology, 2022)
Ischemic stroke is a highly disabling and fatal disease that seriously threatens human life and health. Following ischemic stroke, autophagy plays a key regulatory role as an intracellular catabolic pathway for misfolded proteins and damaged organelles. Mounting evidence shows that astrocytes are strongly linked to the occurrence and development of cerebral ischemia. In recent years, great progress has been made in the investigations of astrocyte autophagy during ischemic stroke. This article summarized the roles and potential mechanisms of astrocyte autophagy in ischemic stroke, briefly expounded the correlations of astrocyte autophagy with apoptosis and necroptosis and its potential protective impact on neurons, and reviewed the astrocytic autophagy-targeted therapeutic methods for cerebral ischemia, aiming to provide new perspectives and strategies for the treatment of cerebral ischemia and provide a reference for the research on cerebral ischemia.